2013
DOI: 10.1073/pnas.1305062110
|View full text |Cite
|
Sign up to set email alerts
|

Causal effect of disconnection lesions on interhemispheric functional connectivity in rhesus monkeys

Abstract: In the absence of external stimuli or task demands, correlations in spontaneous brain activity (functional connectivity) reflect patterns of anatomical connectivity. Hence, resting-state functional connectivity has been used as a proxy measure for structural connectivity and as a biomarker for brain changes in disease. To relate changes in functional connectivity to physiological changes in the brain, it is important to understand how correlations in functional connectivity depend on the physical integrity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
167
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(189 citation statements)
references
References 59 publications
18
167
3
1
Order By: Relevance
“…(iii) It ensures that judgments about similarities in the coupling patterns of frontal areas in humans and macaques are not influenced by interspecies differences in the way that target areas are interconnected with one another. However, it is important to remember that although it is the case that such coupling patterns reflect monosynaptic connections, they do not do so exclusively (15). In addition, a complementary analysis based on partial correlation is shown in SI Appendix, Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(iii) It ensures that judgments about similarities in the coupling patterns of frontal areas in humans and macaques are not influenced by interspecies differences in the way that target areas are interconnected with one another. However, it is important to remember that although it is the case that such coupling patterns reflect monosynaptic connections, they do not do so exclusively (15). In addition, a complementary analysis based on partial correlation is shown in SI Appendix, Fig.…”
Section: Methodsmentioning
confidence: 99%
“…We used fMRI in 25 monkeys and 38 humans to delineate the functional interactions of "decisionmaking regions" with other areas in the brain while subjects were at rest. Such interactions are reliant on anatomical connections between areas (15) and determine the information an area has access to and the way it can influence other areas, and thereby behavior. Each region of the brain has a defining set of interactions, a connectional or interactional "finger-print" (16), that can be compared across species (17)(18)(19).…”
mentioning
confidence: 99%
“…Several factors may support this compensatory strategy, including (i) postlesion training or retraining and (ii) postlesion network reorganization (19)(20)(21). Thus, although lesion studies are useful in documenting altered function after injury, they cannot directly address the role of the hippocampus in the uninjured brain.…”
mentioning
confidence: 99%
“…Other studies have compared structure-function relations across species (Miranda-Dominguez et al 2014). The notion that structural connections shape and/or constrain functional connections is not only supported through comparisons of anatomical and functional connectivity but is also reinforced by interventional studies that have reported changes in functional connectivity resulting from manipulations of the anatomical substrate (Johnston et al 2008;O'Reilly et al 2013). Extending this notion to brain and mental disorders, a large number of studies have attempted to link dysregulation of functional connectivity patterns to underlying disturbances of structural connectivity, e.g., in disrupted hub or rich club connections [reviewed in van den Heuvel and ].…”
Section: Macroscalementioning
confidence: 99%